Effect of γ-Substituted Proline Derivatives on the Performance of the Peptidic Catalyst H-dPro-Pro-Glu-NH2 - Schnitzer, Tobias; Wennemers, Helma (Synthesis, 2018)
Substituents at Cγ of proline are valuable probes to tune the trans/cis ratio of Xaa–Pro bonds. We investigated the effect of Cγ-substituents on the reactivity and stereoselectivity of the peptidic catalyst H-dPro-Pro-Glu-NH2. Derivatives that bear electron-withdrawing and -donating substituents (OH, F, N3, and SMe) at Cγ of the middle Pro-residue were examined. The results show that substituents at a 4R-configured Cγ hardly affect the stereoselectivity of the peptidic catalyst whereas substituents at a 4S-configured Cγ can be used to tune and improve the catalytic performance.
Keywords: proline; peptides; trans/cis isomerization; organocatalysis; conjugate addition reactions